Moral licensing: Another source of rebound? - Elisabeth Dütschke; Manuel Frondel; Joachim Schleich; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
The rebound effect denotes an offset in energy savings that occurs when an individual increases consumption of a good or service following an increase in its efficiency. It has both economic and psychological underpinnings: In addition to the price, income and substitution effects emphasized by economists, psychologists point to the influence of moral licensing, the cognitive process by which individuals justify immoral behavior (e.g. driving more) by having previously engaged in moral behavior (e.g. purchasing a more efficient car). The present review article provides a conceptual and empirical overview of moral licensing, drawing comparisons with economic explanations for the rebound effect. Based on a unifying theoretical model that illustrates how economic and psychological motivations trigger both rebound and moral licensing effects, as well as a review of micro-econometric and experimental evidence, we conclude that consideration of moral licensing is warranted for judging the efficacy of policies targeted at energy consumption and the rebound effect. – – Der Rebound-Effekt kann sowohl ökonomische als auch psychologische Ursachen haben. Zusätzlich zu den von Ökonomen herausgestellten Preis-, Einkommens-, und Substitutionseffekten weisen Psychologen auf den Einfluss von Moral Licensing hin. Dabei handelt es sich um einen kognitiven Vorgang, bei dem 'unmoralisches' Verhalten (z.B. mehr zu fahren) mit einer moralischen Verhaltensweise in der Vergangenheit (z.B. ein effizienteres Auto gekauft zu haben) gerechtfertigt wird. Der vorliegende Übersichtsartikel bietet einen konzeptionellen und empirischen Überblick zu Moral Licensing und präsentiert ein vereinheitlichendes theoretisches Modell, in dem ökonomische und psychologische Motivationen sowohl Rebound- als auch Moral Licensing-Effekte auslösen. Wir kommen zu dem Schluss, dass Moral Licensing bei der Beurteilung der Wirksamkeit von Politikmaßnahmen, die auf die Senkung des Energieverbrauchs abzielen, zu berücksichtigen ist.
Keywords: D12; Q48; 330; substitution effect; income effect; scale effect; moral licensing; moral cleansing